Li Jinhui's kindergarten music textbook and its compatibility with today's preschool music education in China - Huang, Yi; Loo, Fung Chiat; Yeoh, Pei Sze; Indra, Selvarajah (Human Resources Management Academic Research Society (HRMARS), 2023)
Since the beginning of the 20th century, along with China’s preschool curriculum, music education has experienced more than 100 years of development. In China, music is an important subject in promoting children’s physical and mental development. Li Jinhui (1891−1967) was a prolific composer who penned many famous songs and children’s musicals. However, from the late 1920s, he became a controversial figure; his work was termed as “yellow music” by critics due to his popular music compositions being claimed to relate to pornography. While many prior studies have focused on Li’s popular works and children’s musicals, this study revisits his significance in music education in China. This study analyzes an important work, Li’s textbook on the approach and teaching method in kindergarten education published in 1933. Li Jinhui was the first person to publish kindergarten music textbooks according to the official curriculum standard issued by the Nanjing government. The analysis revealed that the approach Li suggested for preschoolers’ music learning is compatible with China’s current goals in music education. The systematically arranged content of this textbook could also solve the problem of inconsistencies in the current curriculum.